Clinical indicators for reporting the effectiveness of patient quality and safety-related interventions: a protocol of a systematic review and Delphi consensus process as part of the international Standardised Endpoints for Perioperative Medicine initiative (StEP). Issue 11 (2nd December 2018) - Bampoe, Sohail; Cook, Tim; Fleisher, Lee; Grocott, Michael P W; Neuman, Mark; Story, David; Myles, Paul; Haller, Guy
Abstract : Introduction: Clinical indicators are used to measure and quantify the safety and quality of patient care. They are also often used as endpoints in clinical trials. Definitions of clinical indicators in common use are extremely heterogeneous, limiting their applicability. As part of the international Standardised Endpoints in Perioperative Medicine initiative, this study will identify clinical indicators by systematically reviewing the anaesthesia and perioperative medicine literature, and will provide consensus, clinically useful definitions for those indicators using a Delphi process. Methods and analysis: An electronic database search will be conducted of Medline (PubMed/OVID), EMBASE and the Cochrane Library in order to meet this review's objectives that are: (1) To identify clinical indicators and their definitions used in randomised controlled trials that assess patient-related quality and safety interventions in perioperative medicine; (2) To select a shortlist of recommended indicators and definitions that are the most suitable for evaluation of quality and safety interventions following an expert-based consensus-gaining process (Delphi method) and (3) To provide a classification scale for each indicator related to its clarity of definition, validity (strength), reliability, feasibility (ease of use) and frequency of use. This systematic review protocol is reported in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidance. Ethics and dissemination: Ethical approval is not required for this systematic review and Delphi process. The results of this study will be disseminated to the anaesthesia and perioperative medicine clinical and academic community through national and international presentations and through publication in a peer reviewed journal. PROSPERO registration number: CRD42016042102.